1998
DOI: 10.1046/j.1365-2885.1998.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, bioavailability and dosage regimen of sulphadiazine (SDZ) in camels (Camelus dromedarius)

Abstract: The pharmacokinetics of sulphadiazine (SDZ) (100 mg/kg, body weight) were investigated in six camels (Camelus dromedarius) after intravenous (i.v.) and oral (p.o.) administration. Following i.v. administration, the overall elimination rate constant (beta) was 0.029 +/- 0.001/h and the half-life (t1/2beta) was 23.14 +/- 1.06 h. The apparent volume of distribution (Vd(area)) was 0.790 +/- 0.075 L/kg and the total body clearance (ClB) was 23.29 +/- 2.50 mL/h/kg. After p.o. administration, SDZ reached a peak plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This is in accordance with other pharmacokinetic data about combinations of sulfonamides and TMP (Nielsen & Gyrd‐Hansen, 1994). The oral bioavailability of SDA and TMP have been calculated for a number of species, such as pigs (Nielsen & Gyrd‐Hansen, 1994; Luther, 1979), cattle (Luther, 1979), chickens (Löscher et al ., 1990), horses (Van Duijkeren et al ., 1994), camels (Kumar et al ., 1998) and Japanese quails (Lashev & Mihailov, 1994). With the exception of the horse, SDA and TMP are well absorbed in most animal species.…”
Section: Pharmacokinetic Parameters After IV (Trisuprime 24%) and mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with other pharmacokinetic data about combinations of sulfonamides and TMP (Nielsen & Gyrd‐Hansen, 1994). The oral bioavailability of SDA and TMP have been calculated for a number of species, such as pigs (Nielsen & Gyrd‐Hansen, 1994; Luther, 1979), cattle (Luther, 1979), chickens (Löscher et al ., 1990), horses (Van Duijkeren et al ., 1994), camels (Kumar et al ., 1998) and Japanese quails (Lashev & Mihailov, 1994). With the exception of the horse, SDA and TMP are well absorbed in most animal species.…”
Section: Pharmacokinetic Parameters After IV (Trisuprime 24%) and mentioning
confidence: 99%
“…Also bacterial resistance to SDA–TPM combinations is increasingly seen for some bacterial species (Salmon et al ., 1995). The pharmacokinetic profile for SDA and TMP has been described in chickens (Löscher et al ., 1990) , camels (Kumar et al ., 1998), cattle (Clarke et al ., 1989), donkeys (Oukessou & Alsouss, 1998), horses (Brown et al ., 1983; Van Duijkeren et al ., 1994), dogs (Sigel et al ., 1981), Japanese quails (Lashev & Mihailov, 1994), carp (Nouws et al ., 1993) and pigs (Søli et al ., 1990; Nielsen & Gyrd‐Hansen, 1994; Garwacki et al ., 1996). The aim of this study was to determine the oral bioavailability and pharmacokinetics of SDA and TMP after oral administration of a new commercial formula (Trimazin 30%, Kela N.V., Hoogstraten, Belgium) in young unfasted, healthy pigs.…”
Section: Pharmacokinetic Parameters After IV (Trisuprime 24%) and mentioning
confidence: 99%
“…The pharmacokinetic profile of SDA and TMP used together has been reported for chicken (Löscher et al, 1990;Batzias et al, 2000;Baert et al, 2003) and ostrich (Abu-Basha et al, 2009). Studies in other species such as swine (Søli et al, 1990;Nielsen & Gyrd-Hansen, 1994;Garwacki et al, 1996;Baert et al, 2001), cattle , camel (Kumar et al, 1998), horse (Brown et al, 1983;, dog (Sigel et al, 1981), donkey (Oukessou et al, 1998), Japanese quail (Lashev et al, 1994) and carp (Nouws et al, 1993) have also been performed. All studies reported a higher volume of distribution (V d ) or clearance (Cl), and a substantially shorter T 1/2 for TMP compared with SDA.…”
Section: Introductionmentioning
confidence: 99%